The effects of China's social environment on women's careers: a qualitative study based on a gender perspective - Yu, Yi (2022)
With the gradual entry of women into the international labour market. The impact of the female workforce on company strategy is becoming increasingly evident. Although more and more companies are becoming aware of the importance of managing female employees, professional women still face obstacles to their job development from different levels. Especially in China, due to its cultural peculiarities (such as the Confucian ideology), the career development of Chinese women is more particularly influenced by a different social and cultural context. This study adopts a qualitative research method to interview 20 Chinese career women of different age groups. Based on their descriptions of their workplace lives, the data is summarised, and the factors that influence their career development are then synthesised. The results of the data analysis are also discussed in relation to gender-related theories. As a result, the study found that Chinese working women's career development is influenced by three levels: social, organisational and family, and that the factors affecting their development mainly stem from social policies and contexts, stereotypes of women and the division of gender roles. At the same time, this study found that some of the ideas put forward by human capital theory are not applicable to the Chinese context, and that gender queuing and gender stratification still exist in the Chinese workplace.